2019
DOI: 10.3389/fbioe.2019.00197
|View full text |Cite
|
Sign up to set email alerts
|

Nanotheranostics Targeting the Tumor Microenvironment

Abstract: Cancer is considered the most aggressive malignancy to humans, and definitely the major cause of death worldwide. Despite the different and heterogenous presentation of the disease, there are pivotal cell elements involved in proliferation, differentiation, and immortalization, and ultimately the capability to evade treatment strategies. This is of utmost relevance when we are just beginning to grasp the complexity of the tumor environment and the molecular “evolution” within. The tumor micro-environment (TME)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 172 publications
(238 reference statements)
0
57
0
Order By: Relevance
“…CLSM analysis showed that the nanoparticles were accumulated mainly in the exterior regions compared to core regions with limited perfusion, favorable for antigen delivery to immune cells also located in tumor margins. 61,62 Finally, the biosafety of different nanoparticle formulations was analyzed. Heart, liver, kidney, lung, spleen, primary and secondary tumors were collected at the end of treatment for H & E staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CLSM analysis showed that the nanoparticles were accumulated mainly in the exterior regions compared to core regions with limited perfusion, favorable for antigen delivery to immune cells also located in tumor margins. 61,62 Finally, the biosafety of different nanoparticle formulations was analyzed. Heart, liver, kidney, lung, spleen, primary and secondary tumors were collected at the end of treatment for H & E staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, pegylation of drug-loaded liposomes not only improved their blood circulation, but also increased the accumulation of the drug in the tumor [43]. Furthermore, active targeting of the nanomedicines improves greatly their efficacy (reviewed in [40,[46][47][48]). With that purpose, several biological ligands could be bind to nanomaterials, including antibodies, such as cetuximab, an FDA approved antibody against anti-epidermal growth factor receptor (EGFR) used in clinical practice for cancer treatment; glycoproteins, such as the iron-binding transferrin; polysaccharides, such as hyaluronic acid for CD44 targeting; peptides, such as arginylglycylaspartic acid (RGD) for integrins targeting; aptamers, such as AS-1411 G-rich DNA aptamer for nucleolin targeting; or other small molecules, such as folate ( [49][50][51][52][53][54][55][56][57][58][59][60], reviewed in [48]).…”
Section: Introductionmentioning
confidence: 99%
“…However, this dose increase could trigger undesired side effects harmful to the patients. This limitation makes NPs ideal candidates for the delivery of cancer immunotherapy since they follow different pharmacokinetics and pharmacodynamics compared to free drugs [60,61].…”
Section: Introductionmentioning
confidence: 99%